Perception Of Pregnant Mothers And Willingness To Vaccinate Against Covid-19 - Mariene Wiwin Dolang (Lembaga Pengembangan Kinerja Dosen, 2022)
Pregnant women are a group that is vulnerable to Covid-19 due to physiological changes that result in changes in response to Covid-19 infection. Pregnant women with Covid-19 are at risk for preeclampsia, stillbirth, premature birth, and maternal death. The magnitude of the impact, it is necessary to have a Covid-19 vaccine to reduce the incidence and reduce the severity caused by Covid-19, especially in pregnant women. This study aims to determine the relationship between knowledge, perception, and disease history with the willingness of pregnant women to take the Covid-19 vaccine. This research is a descriptive analytic with a cross sectional study design. The population is all pregnant women in the second and third trimesters who are in the Work Area of ​​the Tomalehu Health Center, West Seram Regency, as many as 41 respondents. The sample is pregnant women in the second and third trimesters who are in the Working Area of ​​the Tomalehu Health Center as many as 37 respondents with purposive sampling. Processing and analysis using Chi Square test. The results showed that there was a relationship between perception (p = 0.000) and the willingness of pregnant women to vaccinate against Covid-19. Researchers suggest that health workers and the government should increase the socialization of giving vaccinations to pregnant women. vaccination coverage can be increased